A generative design system applied to Sizaís school of architecture at Oporto - Caldas, Luisa (2011)
A new generative design system based on a genetic algorithm is tested within the framework of Alvaro Siza’s School of Architecture at Oporto, Portugal. The system works over a detailed three-dimensional description of the building and uses natural lighting and overall environmental performance as objective functions to guide the generation of solutions. This paper researches the encoding of architectural design intentions into the system, using constraints derived from Siza’s original design. Experiments using this generative system were performed on three different geographical locations to test the algorithm’s capability to adapt solutions to different climatic characteristics within the same language constraints.